STRES KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Setyawati, Novita Wahyu; Aryani, Nur Ade; Ningrum, Endah Prawesti (Economic Faculty, Attahiriyah Islamic University, 2018)
This study aims to determine the effect of work stress and work discipline on employee performance at Manggarai Station, South Jakarta. The type of research used is probability sampling with a quantitative approach. The sample used in this study used a simple random sampling technique. The data obtained are primary data from the results of respondents' answers to questionnaires distributed by 115 respondents and processed using the SPPS (Statistic Product and Service Solution) software program 17. In the f test the variable Job Stress and Work Discipline together (simultaneous) affect the Employee Performance. The results of the study show that in the t test (partial) the Job Stress variable negatively affects Employee Performance and Work Discipline variables have a positive effect on Employee Performance. Keywords: work stress, work discipline, employee performance